MANFAAT KERANGKA KERJA KONSEPTUAL AKUN KEUANGAN BAGI AKUNTAN PUBLIK DALAM MELAKSANAKAN PEKERJAANNYA - Michael Iskandar; Sylvia Fettry (Center for Economic Studies Universitas Katolik Parahyangan, 2008)
The conceptual framework for financial accounting and reporting was developed to achieve standardization in financial accountant practices. This framework consists of three revers, which are (1) objectives of financial reporting, (2) elements of financial statements and quality characteristics of accounting information, and (3) recognition and measurement concepts. In Indonesia, the main work of a public accountant is to do financial audits on business entities, followed by attestation by the public accountant to endorse (or not) the business entities' statements. Analyses done both upon the conceptual framework and the work of a public accountant shows that the framework is helpful to the public accountant's work, because (l) the financial accounting standards used by the public accountant were created based on the conceptual framework, and (2) in the case that no standards or rules have been set, then the conceptual framework provides guidance to the public accountant. An example is provided to enhance understanding.